Tantangan Menuju Masyarakat Inklusif: Apakah Ketimpangan Ekonomi dan Korupsi Mengancam Hak Asasi Manusia? - Putri, Nimas Ayu Eka; Oktaviana, Siska Wahyu; Rajagukguk, Marlon Brando; Kartiasih, Fitri (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Economic inequality and political corruption are two structural issues that significantly affect the protection of human rights, particularly in developing countries such as Indonesia. Economic inequality, characterized by unequal income distribution and limited access to basic services, exacerbates the vulnerability of marginalized communities. Meanwhile, political corruption undermines democratic institutions, fosters injustice, and restricts public access to fundamental rights. This study aims to analyze the impact of economic inequality and political corruption on the Human Rights Index (HRI) in Indonesia during the period 1993–2023 using the Error Correction Model (ECM) approach. The results indicate that both in the short and long term, economic inequality measured by the Gini Coefficient and political corruption levels significantly contribute to the decline in HRI. In the long term, a 1% increase in the Gini Coefficient reduces the HRI by 0.59%, while a 1% rise in the Political Corruption Index lowers the HRI by 5.68%. This study underscores the importance of inclusive and transparent institutional reforms to address these structural challenges and improve the protection of human rights in Indonesia.